COMPARATIVE TRANSLATION OF PHRASELOGICAL UNITS IN DETECTIVE NOVEL OF ARTHUR CONAN DOYLE “THE ADVENTURE OF SHERLOCK HOLMS” (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article analyzes the comparative translation of phraseological units in the detective work of Arthur Conan Doyle“THE ADVENTURE OF SHERLOCK HOLMS” with a focus on the challenges and strategies involved in rendering these linguistic expressionsinto Uzbek language. Phraseological units, as fixed expressions with figurative meanings,play an important role in enriching the narrative and character development in Conan Doyle’s works. The study explores how these units are translated from English into Uzbek language, highlighting the nuances of meaning, and stylistic effects. Drawing on examples from Conan Doyle's detective plays, particularly the Sherlock Holmes series, the research employs a comparative analysis method to investigate the preservation of idiomatic meaning, equivalence, and adaptation in translation. The findings reveal that successful translation requires a deep understanding of both source and target languages, as well as the cultural contexts they represent. This study contributes to the broader field of translation studies by offering insights into the challenges and best practices for translating phraseological units in literary texts, ensuring the retention of their original essence and impact.